Penerimaan Pesan Persuasif dari Perspektif Elaboration Likelihood Model : Iklan Layanan Masyarakat Himbauan Berhenti Merokok - Chairun Nisa Dwi Putri; Alvin Gus Abdurrahman Wahid; Irwansyah Irwansyah (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
The number of smokers among Indonesian teenagers continues to increase every year. Public service advertisements (PSA) for smoking prevention must be delivered with the right approach to be accepted in the minds of the audience. This study aims to expand on previous research on smoking prevention PSAs by testing the concept of the Elaboration Likelihood Model theory. The research method applied is exploratory qualitative which is complemented by the results of in-depth interviews with 4 participants of postgraduate students of communication science at the University of Indonesia. The results of this study indicate that attitudes towards issues and personal relevance are the factors that most influence the acceptance of persuasive messages on PSAs that prohibit smoking #SuaraTanpaRokok. Repetition can be used to increase the effectiveness of a given persuasive message.